2001
DOI: 10.1007/s11627-001-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Clonal propagation of Arnica montana L., a medicinal plant

Abstract: Micropropagation of Arnica montana L. using Murashige and Skoog (MS) medium supplemented with N 6 -[2-isopentenyl]adenine (2iP), zeatin and a-naphthaleneacetic acid (NAA) in different concentrations does not ensure the formation of a high number of regenerated plants; a maximum of 3.2 neoplantlets per explant were obtained. After 4 wk of culture on medium with zeatin (4.5 mM ) and NAA (5.3 mM ), plants were 3.06 cm in length. The following step was to improve the clonal propagation of this species. Micropropag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In addition, it is considered extinct in Hungary and Lithuania. 3 Arnica montana grows in nutrient-poor siliceous meadows or clay soils. It mostly grows on alpine meadows and up to nearly 3,000 m (9,800 ft).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is considered extinct in Hungary and Lithuania. 3 Arnica montana grows in nutrient-poor siliceous meadows or clay soils. It mostly grows on alpine meadows and up to nearly 3,000 m (9,800 ft).…”
Section: Introductionmentioning
confidence: 99%
“…It is a phenolic compound known for its properties as a promoter of plant growth [13,14]. Studies focusing on the effects of phloroglucinol on in vitro cultures have shown to enhance growth and rate of axillary shoots in several woody plants, to initiate adventitious roots on in vitro shoots of different woody species, to enhance survival of meristems and/or shoot tips in vitro [15,16,17], to enhance shoot multiplication and elongation [18,19,20,21,22], and root proliferation [23,24,25,26,27,28], to embryogenesis induction [29,30] and to improve recovery of cryopreserved protocorms [31]. A synergistic effect with auxin during root initiation has also been reported [17,32,13,33,14].…”
Section: Introductionmentioning
confidence: 99%